L’ekphrasis dell’Hypnerotomachia Poliphili tra evidentia e narratio .......... 109 - Maffei, Sonia (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
The essay deals with the topic of ekphrasis in the Hypnerotomachia Poliphili and identifies some descriptive strategies used by Francesco Colonna. The text proposes the analysis of the different types of vision present in many passages of the novel, and identifies the presence of circular structures used to separate some particularly important descriptions (such as the Pyramid, the Magna Porta, the temple of Venus Physizioa). The study also analyses the descriptive lexicon and highlights some passages in which the search for correspondences between the style of the objects described and the style of the description produces refined experiments in the “theory of decor”.